A Case of Postpartum Anogenital Mammary-Like Gland Tumor with Focal Lactational Features: A Nomenclature Issue - Sakinah A. Thiryayi; Marjan Rouzbahman; Danny Ghazarian (Case Reports in Pathology)
Mammary-like glands (MLG) are considered to be a normal constituent of the anogenital region and can give rise to tumors with variable morphology that may be difficult to classify. We present a case of an anogenital mammary-like gland tumor in a breastfeeding woman showing morphological variation with lactational change, an unusual finding. We discuss the differing terminology used to report these tumors and the variation in assignment of their origin to MLG or ectopic breast tissue.